Análise das alterações genéticas e epigenéticas dos tumores gástricos infectados por Helicobacter pylori e v rus Epstein-Barr - Ferrasi, Adriana Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Gastric cancer (GC) is one of the most common cancer types and it is associated with high mortality frequencies. Although a decrease in the worldwide incidence is observed, the prognosis of this disease still remains poor, mainly when the diagnosis is carried out at advanced stages. Recent evidences have identified DNA methylation as an important mechanism for tumor suppressor gene inactivation. Helicobacter pylori infection is considered one of the most important etiological factors and the CagA gene is associated with more severe pathologies including cancer. Likewise, EBV is another infectious agent that has been associated with gastric carcinoma in at least 10% of the cases. In this study, we determined the promoter methylation status of the CDH1, DAPK, COX2, hMLH1 and CDKN2A and MSI frequency in 89 primary gastric carcinomas and correlated the findings with the presence of H. pylori and EBV infections and also with clinicopathological features of gastric carcinomas. COX2 was the most frequently hypermethylated gene (63.5%) in these patients, followed by DAPK (55.7%), CDH1 (51%), CDKN2A (36%) and hMLH1 (30.3%). In this study, MSI was correlated with hMLH1 methylation, as shown before, and there was an inverse correlation between DAPK hypermethylation and MSI. Also, MSI was inversely correlated with H. pylori CagA+, providing new evidence for the association of MSI and better prognosis.
Keywords: Cancer; Tumores; Metilação; Câncer gástrico; Tumor gástrico; Instabilidade de microssatelites; Gastric cancer